1983
DOI: 10.1095/biolreprod28.2.425
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Factors Affecting the Success of Human Fertilization in Vitro. II. Influence of Semen Quality and Oocyte Maturity on Fertilization and Cleavage

Abstract: The incidence of in vitro fertilizationwas analyzed with respect to the degree of cumulus dissociation (expansion) at the time of oocyte recovery and also the semen quality.Of the oocytes surrounded by perfectly ("++") or moderately ("+") p<0.ool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…The degree of cumulus expansion did not necessarily correlate with nuclear maturation, as the maturation rate of oocytes whose cumulus remained compact after IVM was not significantly different from that of oocytes whose cumulus became expanded during IVM. However, these two conditions are necessary, as Testart et al [58] found that a higher proportion of human oocytes were able to cleave following IVF when cumulus expansion was complete.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of cumulus expansion did not necessarily correlate with nuclear maturation, as the maturation rate of oocytes whose cumulus remained compact after IVM was not significantly different from that of oocytes whose cumulus became expanded during IVM. However, these two conditions are necessary, as Testart et al [58] found that a higher proportion of human oocytes were able to cleave following IVF when cumulus expansion was complete.…”
Section: Discussionmentioning
confidence: 99%
“…CUMULUS CELL miR-378 IMPAIRS OOCYTE MATURATION one of the primary measures of oocyte quality, creating a microenvironment favorable for nutrients and paracrine factors to reach the oocyte to alter gene expression and allow meiotic progression (52). During ovulation, the expansion of cumulus facilitates the release of a COC from the follicle and helps to maintain the viability of the oocyte during its passage in the oviduct (22,40).…”
Section: E530mentioning
confidence: 99%
“…Evidence has emerged to support the involvement of various locally produced factors as co-regulators of folliculogenesis and oocyte nuclear and cytoplasmic maturation in addition to extrinsic regulation by pituitary gonadotropins and metabolic hormones [5]. Optimal expansion of the cumulus mass appears to be essential for cytoplasmic maturation [6,7]. In the bovine, the induction of cumulus expansion prior to fertilization increased the incidence of oocyte penetration [8].…”
Section: Introductionmentioning
confidence: 99%